Readiness to change towards accredited public health centres (PHCs) in West Lombok - I Made Santiana; Ni Made Sri Nopiyani; Dyah Pradnyaparamita Duarsa (Public Health and Preventive Medicine Archive, 2018)
Background and purpose: The 2016 Report of Performance Accountability of Government Agencies, Ministry of Health of Indonesia showed only a small proportion of public health centres (PHCs) are accredited. In West Lombok District, some PHCs are not accredited. This study aims to examine factors associated with PHC’s staff readiness for accreditation. Methods: A cross-sectional survey was employed involving seven non-accredited PHCs. A total of 165 out of 310 PHC’s staff were recruited using a systematic random sampling. Data was collected from February to March 2017. Self-administered questionnaire was used to collect data on socio-demographic characteristics, duration of service, content, process, and context changes, individual attributes, and readiness to change. Logistic regression was applied to examine the association between readiness to change with independent variables. Results: As many as 72.1% of respondents are ready to change. From the change efficacy and appropriateness dimensions, as many as 46.1% and 97.0% of respondents are ready to change. Multivariate analysis shows an association between readiness to change with administrative systems (AOR=4.47;95%CI:2.05-9.74) and working procedure (AOR=2.95; 95%CI: 1.19-7.30). There is no significant association between readiness to change with technological improvement, promotional strategy, staff engagement, organisational commitment and managerial support from health offices. Conclusions: The readiness to change among PHC’s staff is high. The availability of working procedure and administrative systems improves PHC’s staff readiness for the accreditation. These findings suggest the importance of inclusion of all PHC’s staff during the accreditation processes.